The Impact of Creative Problem Solving Strategy VS Learning Cycle Model and Cognitive Style on The Understanding of Comparison Concept - Muhammad Ainul Fudo'il; I Nyoman Sudana Degeng; Nurmida Catherine Sitompul (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2019)
This study aims to examine the differences in the understanding of the comparison concept in groups of students who take realistic mathematics learning through the Creative Problem Solving (CPS) and Learning Cycle Model (LCM) strategies. It also examines the differences in the understanding of comparison concept between groups of students who have Field Independent (FI) and Field Dependent (FD) Cognitive Style. Lastly, it examines whether there is an interaction between learning strategies and Cognitive Style towards the students’ understanding of the concept of comparison. This study uses quasi-experimental research design, with 2x2 factorial design pretest-posttest nonequivalent control group design. Data analysis uses two-way ANOVA by utilizing SPSS statistical software version 22 for windows. The subjects of this study were 53 seventh-grade students of Islamic junior high school (MTs) Azzainabiyah Pramian Sampang Madura, consisting of 2 classes (experimental class and control class) with non-random assignment. The instrument used in this study is the Cognitive Style test called GEFT (Group Embedded Figure Test) and learning outcomes test. The results of this study indicate that there is no difference in the understanding of the concept of comparison in groups of students who take realistic mathematics learning through CPS and LCM strategies. There is a difference in the understanding of the concept of comparison between groups of students who have FI and FD cognitive style. There is no interaction between the strategy of learning with the cognitive style possessed by students towards the understanding of the concept of comparison.